Vendor Certification and Appraisal: Implications for Supplier Quality - Hwang, Iny; Radhakrishnan, Suresh; Su, Lixin (Nancy) (Management Science, 2006)
We examine the buyer's problem of inducing the supplier's quality effort using two arrangements: the appraisal regime and the certification regime. In the appraisal regime, the buyer inspects the units supplied and either charges a penalty for defective units identified during inspection or pays the unit price for good units. In the certification regime, the supplier obtains vendor certification and the buyer pays the unit price for all units supplied. The inspection technology and the certification process provide noisy information on the supplier's quality effort. In the appraisal regime, the buyer implements the supplier's high-quality and low-inspection. The supplier's expected profit is greater than his reservation profit because of an additional agency cost: The buyer has to prevent the supplier from performing unwanted/preemptive inspection (which gives rise to indirect costs from delay, etc.). This additional agency cost arises precisely when the effectiveness of inspection is high. This provides a moral-hazard-based rationale for the increasing use of certification (such as ISO 9000) in spite of (in fact, because of) the increasing effectiveness of inspection. The potential for additional agency cost incurred by the buyer in the appraisal regime highlights an indirect cost associated with inspection.